PENDAMPINGAN KEGIATAN RUMAH SAKIT UMUM DAERAH DI PROVINSI JAWA TIMUR DALAM PENYIMPANAN, PENGELOLAAN, DAN PENGEMASAN LIMBAH BAHAN BERBAHAYA DAN BERACUN (B3) - Nisa', Syadzadhiya Qothrunada Zakiyayasin; Sitogasa, Praditya Sigit Ardisty; Murti, Restu Hikmah Ayu; Jawwad, Muhammad Abdus Salam; Putri, Marsanda Amelia; Fachrudin, Rizal (Environmental Engineering Journal of Community Dedication, 2025)
Hospital hazardous waste (B3) management is crucial to avoid negative impacts on health and the environment. This community engagement aimed to improve B3 waste handling capacity in a regional hospital in East Java. Activities included site observation, technical discussions, SOP development, labeling training, and digital reporting via the Festronik system. Observations revealed issues in waste labeling, characterization, and logbook documentation. Interventions successfully improved labeling according to waste properties, developed technical SOPs, and fulfilled storage requirements based on Government Regulation No. 22 of 2021 Article 419 paragraph (4). Enhancements such as emergency response tools and updated signage further supported safe and compliant waste management. This program is expected to strengthen sustainable B3 waste governance in the healthcare sector.